Analisis Bahan Kimia Obat Parasetamol pada Jamu Pegal Linu yang dijual di Kecamatan Pasar Jambi, Kota Jambi - Siti Marwah Lestari; Widya Twiny Rizki; Rahmadevi; Nindi Sepdina Yanti (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
Background: Chemical drugs that were often added to pegal linu herbal medicine was paracetamol. Paracetamol added as analgesic. Objective: This study aims to analyze qualitatively the content of Paracetamol in the pegal linu herbal medicine, which is sold in Pasar Jambi District, Jambi City. Method: This study was conducted qualitatively, samples were taken by purposive sampling, and 8 samples (SA, SB, SC, SD, SE, SF, SG, and SH) were selected from pegal linu medicine that met the inclusive criteria. Samples were tested organoleptically, microscopically, spot test, and TLC. Results: In the organoleptic test, all herbs were in powder form, SA had a brownish-yellow color with an aromatic odor, SB had a light brown color with an aromatic odor, SC had a greenish-brown color with an aromatic odor, SD had a light brown color with an aromatic odor, SE had a yellowish-brown color with an aromatic odor, SF has a yellowish-brown color with an aromatic odor, SG has a light brown color with an aromatic odor, SH has a greenish-brown color with an aromatic odor. In the spot test, no herbs were found that had the same color reaction as paracetamol. In the TLC test, there were several herbs that had the same Rf value as standard paracetamol. In the 1st, 2nd, and 3rd tests, the Rf value of paracetamol respectively were 0.36; 0.33; and 0.40. Meanwhile, in the sample, it was found that the Rf value was the same as that of paracetamol. In the first test, the samples coded SD and SG, in the second test there were none, in the third test, the herbal medicine samples coded SC and SD. Conclusion: Pegal linu herbal medicine didn’t contain paracetamol.